Musculoskeletal discomfort (MSD) in female office workers: An exploratory investigation - Ismail Maakip; Peter Voo Su Kiong; Azizi Yahaya (PENERBIT UniMAP, 2023)
Predictors associated with musculoskeletal discomfort (MSD) are multi-factorial, including physical, psychosocial, and individual factors. However, with most of the studies on musculoskeletal disorders being undertaken in developed countries; it is plausible that the findings might not be relevant due to differences in work culture and organizational practices in various developing countries. Given this, the current study aimed to examine the prevalence rate of MSD among female office workers in public organizations. A questionnaire survey was employed to measure job satisfaction, work-life balance, mental health, and MSD levels among female office workers (N=333) from four public sector organizations. The 6 months MSD prevalence was 93.4% (95%CI = 90.9-95.8%). Besides, the most frequently experienced MSD among participants in this present study was on the neck/shoulder (92%), lower back (87.5%), lower extremity (82.4%), and hand/fingers (75%). The findings suggested that female office workers in Malaysia did experience MSD and suffer from it in various body regions. In addition, the results further demonstrate the need to develop MSD risk management in the workplace, particularly among female office workers. Nevertheless, further examination of MSD in various types of occupations that employed women to minimize MSD at the workplace is also needed.